EFEKTIVITAS KELEMBAGAAN PASAR MODAL SYARIAH DALAM MENDUKUNG PERTUMBUHAN INDUSTRI KEUANGAN SYARIAH DI INDONESIA - Ahmad Junaidi; Ahmad Rezky Adenan; Muhammad Mualifurrahmi Arramidly (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effectiveness of Islamic capital market institutions in supporting the growth of the Islamic financial industry in Indonesia. The research employs a qualitative approach using a library research method, utilizing secondary data derived from academic journals, books, laws and regulations, fatwas, and official reports published by the Financial Services Authority (OJK), the Indonesia Stock Exchange (IDX), the National Sharia Council–Indonesian Ulema Council (DSN-MUI), the National Committee for Islamic Economy and Finance (KNEKS), and other relevant institutions. The findings indicate that the effectiveness of Islamic capital market institutions is determined by the quality of regulations, supervisory effectiveness, inter-institutional coordination, investor protection, and innovation in Sharia-compliant investment products. The synergy among OJK, IDX, KSEI, KPEI, and DSN-MUI has contributed to establishing a transparent, secure, and Sharia-compliant Islamic capital market system. Nevertheless, several challenges remain, including the low level of Islamic financial literacy and inclusion, limited product innovation, and emerging digital risks. Therefore, strengthening regulations, enhancing inter-institutional coordination, expanding public education, utilizing digital technology, and developing innovative Sharia investment products are essential to enable the Islamic capital market to make a greater contribution to the growth of Indonesia's Islamic financial industry.